(untitled) (Globalization and Business, 2018)
The article focuses on the role of FDI in Georgia’s and the upgrading of the country’s location advantages, on the one hand, and with the development of domestic firms’ownership advantages on the other hand. economic development. Based on Investment Development Path, research shows that Georgia is on the second level of its development (see chart 1), which means that inflow investments are prevailing on outflow investments and the country is still progressing based on nonmodern technologies based economy. It can largely explain the role of the Government of Georgia in the evolution of the competitiveness of Georgian enterprises and of Georgia as a production location. It also predicts the direction of Georgian outward FDI to neighbor countries and highlights the relevance of the twoway relationship between inward FDI Attracting FDI to Georgia is an issue of major importance nowadays. Georgia has a lot of advantages to promote its economy; however, the small efforts done for the promotion of local savings to transform it to the investments is hinder the economic development of the country. Foreign Direct Investment works as a locomotive to enlarge the transfer of technology, skills and access to export markets. It can decrease unemployment and increase employment; contribute to a higher GDP through higher levels of productivity.